Measurement and simulation of pressure drop across replicated porous aluminium in the Darcy-Forchheimer regime - Otaru, A.J.; Morvan, Herve; Kennedy, Andrew R. (Elsevier, 2018)
Experimental measurements of the pressure drop across porous metals have been compared with computational fluid dynamics simulations, for the first time, for structures typified by large pores with small interconnecting “windows”. Structural information for the porous structures was obtained from X-ray computed tomography and a robust methodology for developing a representative volume element is described. The modelling approach used was able to reliably predict the pressure drop behaviour within the Forchheimer regime. The methodology was extended to simulate flow through geometrically-adapted, “semi-virtual” pore structures and this approach could prove to be an invaluable tool in the design of porous metal components for applications involving fluid flow.